Gliadin-primed CD4+CD45RBlowCD25− T cells drive gluten-dependent small intestinal damage after adoptive transfer into lymphopenic mice. Issue 12 (10th August 2009) - Freitag, T L; Rietdijk, S; Junker, Y; Popov, Y; Bhan, A K; Kelly, C P; Terhorst, C; Schuppan, D
Abstract : Background and aims: Coeliac disease is a common small intestinal inflammatory disorder that results from a breach of intestinal tolerance to dietary gluten proteins, driven by gluten-reactive effector T cells. We aimed to assess the pathogenic role of gluten-reactive T cells and to generate a model of gluten-induced enteropathy. Methods: CD4+CD25− T cell fractions were adoptively transferred into lymphopenic mice, leading to "baseline" small intestinal inflammation. Results: Rag1−/− recipients of gliadin-presensitised CD4+CD45RBlowCD25− T cells, but not CD4+CD45RBhigh naive T cells, gained less weight and suffered from more severe duodenitis when challenged with oral gluten than recipients on gluten-free diet, or recipients of control (ovalbumin)-presensitised T cells. This was accompanied by deterioration of mucosal histological features characteristic of coeliac disease, and increased Th1/Th17 cell polarisation in the duodenum and the periphery. Interestingly, reintroduction of a gluten-free diet led to weight gain, improvement of histological duodenitis, and a decrease in duodenal interferon γ and interleukin 17 transcripts. Moreover, B cell-competent nude recipients of gliadin-presensitised CD4+CD45RBlowCD25− T cells produced high levels of serum anti-gliadin immunoglobulin A (IgA) and IgG1/IgG2c only when challenged with oral gluten. Conclusions: CD4+ T cell immunity to gluten leads to a breach of oral gluten tolerance and small intestinal pathology in lymphopenic mice, similar to human coeliac disease. This model will be useful for the study of coeliac disease pathogenesis, and also for testing novel non-dietary therapies for coeliac disease.